Tinjauan Ekonomi Syariah Terhadap Persaingan Industri Usaha Pakaian Muslimah: Studi Kasus di Toko Alfabe Clothing - Fatimatus Zahro; Mahfud Ilham Dzikrulloh; Uswatun Chasanah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The existence of a company cannot be separated from internal and external influences. The industrial environment is a company's internal and external factors that can pose threats and create opportunities. This research aims to analyze the internal and external environment, especially in the industrial competitive environment at the Alfabe Clothing Muslimah Clothing Store. Analysis of the industrial competitive environment is carried out using descriptive qualitative methods. The five factors of competitive advantage, which are very influential, are the bargaining power of buyers and the level of rivalry between existing competitors. The findings of this research explain that the industrial environment can compete well and have a positive impact on company performance to gain profits without committing fraud and complying with principles in accordance with Islamic teachings such as competing fairly, and behaving siddiq, tabligh, amanah, and fathanah.